Vertical heterogeneity of hydrocarbon-degrading bacteria in a core sediment sample from the Central Indian Ridge - Hao, Tong; Cui, Zhisong; Luan, Xiao; Zhou, Guangzhu; Li, Yingchao; Liu, Jinyan; Chen, Junhui; Wang, Zongling (Frontiers in Marine Science, 2023)
Hydrocarbons are ubiquitous in marine environments, and might fuel hydrocarbon-metabolizing microbes in the ocean. Numerous studies have documented the microbial hydrocarbon degradation in water columns and deep-sea surface sediments. However, the degradation potential and biogeochemical cycle of hydrocarbons in the enormous subsurface sediments remain largely unknown. Here, we used two different hydrocarbons, n-hexadecane (HEX) and methylcyclohexane (MCH), to investigate the distribution and diversity of hydrocarbon-consuming bacteria in a core sediment sample derived from the Central Indian Ridge (CIR), which is adjacent to mid-ridge hydrothermal vents of the Indian Ocean. We revealed different vertical profile of HEX- and MCH-degrading bacteria in the core sediment. Specifically, HEX-degrading bacteria are universally distributed, while MCH-degrading bacteria are only stratified in intermediate layer of the core sediment. Changing factors including dissolved oxygen might affect the natural distribution of different hydrocarbon consumers. Furthermore, we found that a novel species of the genus C1-B045 might play a pivotal role in metabolizing MCH in the CIR deep biosphere. Through amino acid identity comparison with published sequences, we suggested that C1-B045 harbors two novel classes of cyclohexanone monooxygenases involved in MCH metabolism. This study sheds light on the structure and function of hydrocarbon-consuming microbes in deep biospheres.